2021
DOI: 10.1186/s12883-021-02144-5
|View full text |Cite
|
Sign up to set email alerts
|

Venous hypertension caused by a meningioma involving the sigmoid sinus: case report

Abstract: Background Intracranial venous hypertension has been associated with a few cases of meningioma secondary to compression of the venous sinus. This is the rare case of small meningioma involving the sigmoid sinus leading to intracranial venous hypertension mimicking venous thrombosis. Case presentation A 39-year-old woman suffered visual dysfunction due to bilateral papilledema. Noncontrast head computed tomography (CT) showed no intracranial space-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…That is the reason why venographic studies are indicated in patients with a clinical diagnosis of IIH [ 4 ]. Our patient’s final cause of her lateral sinus occlusion turned out to be external compression of the lateral sinus by an MEP, which is very rare [ 5 ]. The final correct MRI interpretation was made with a follow-up imaging study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is the reason why venographic studies are indicated in patients with a clinical diagnosis of IIH [ 4 ]. Our patient’s final cause of her lateral sinus occlusion turned out to be external compression of the lateral sinus by an MEP, which is very rare [ 5 ]. The final correct MRI interpretation was made with a follow-up imaging study.…”
Section: Discussionmentioning
confidence: 99%
“…It may cause an increase in ICP due to its mass effect. Venous hypertension resulting in an increase in ICP is rare and only a few cases have been reported secondary to compression of the venous sinus [ 5 ]. We are reporting a rarer case of increased ICP due to external compression of the venous sinus by a rare type of meningioma, meningioma en plaque (MEP).…”
Section: Introductionmentioning
confidence: 99%
“…Sumi et al . presented a case of meningioma invading the sigmoid sinus, which resulted in intracranial hypertension due to venous hypertension [ 11 ]. Both cases involved low-grade solid, fibrous tumors, which potentially caused venous outflow obstruction or severe stenosis of the venous sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Intraluminal causes of VS include cerebral vein and dural sinus thromboses as well as subocclusive or occlusive arachnoid granulations. Extraluminal, intracranial causes appear to be less common and are primarily described secondary to brain herniation syndromes, though any space-occupying lesion, such as a neoplasm, may cause VS. 8 9 Extraluminal, extracranial causes of VS with significant neurological symptoms are primarily traumatic in origin, for example, venous impingement due to displaced bones after traumatic injuries. Some atraumatic causes of extraluminal, extracranial VS with significant neurological symptoms have been described, such as Eagle's Syndrome and Jugular Bow-Hunter's syndrome.…”
Section: Background and Pathophysiologic Mechanisms Of Intracranial V...mentioning
confidence: 99%